Ectopic pregancy in a previous cesarean scar - Garví Morcillo, Javier (2022)
Ectopic pregnancies in the scar of previous cesarean section are an infrequentpathology. They represent the rarest form of ectopic gestation and occur in 1 in2.000 pregnancies. In recent decades there has been an increase in its incidencerelated to the increase in the number of cesarean sections. Its inconsistent clinicalpresentation may delay its diagnosis, so it requires a high degree of suspicion for itsidentification. The diagnosis is mainly made with transvaginal ultrasound, by findingof the gestational sac in the hysterotomy scar. The scarcity of cases reported in theliterature makes it impossible to standardize correct treatment. The insufficientinformation available together with the potential serious complications make thispathology a challenge for every specialist. We present a case of ectopic pregnancyin the scar of a previous cesarean section which was diagnosed ultrasonographicallyand resolved with medical treatment with methotrexate. The importance of followup,both clinical and with ultrasound and βhCG levels until complete resolution, isevident.